COVID-19: Understanding a New Disease Through Global Efforts - Akçay, Arzu; Kınoğlu, Kubilay; Özgün Şahin, Ayşe (The Bulletin of Legal Medicine, 2020)
COVID-19, the disease caused by the novel coronavirus SARS-CoV-2 which was first reported in Wuhan, China in December 2019, is seen to have left its mark in the history with a global pandemic. As a novel member of the coronavirus family, SARS-CoV-2 represents a new kind of sickness in regard to viral pathogenesis and tissue changes. To comprehend the pathogenicity of the virus totally, one has to follow the pathways which a virus travels and inflicts damage through. What starts out as a simple fever and coughing carries the potential to lead to shock, multi – organ failure and death even in the most unsuspected of cases. When faced with a challenge as contagious, deadly and widespread as this, one should put all the efforts that they have in order to overcome this obstacle. In the case of COVID-19 this cumulative effort has shaped itself into a globalized form. In an attempt to see the wider picture as to the whole pathogenesis of COVID-19,  the medical and scientific society should recall the importance of a fundamental discipline, namely, autopsy. Even though, conducted in small numbers at the time, autopsies of COVID-19 cases have provided the literature with many important information. The role of autopsy in understanding disease, the immune system and pathogenesis is one that should not be disregarded and conversely, should be further developed and praised. The same ideology would apply to COVID-19 and any further pandemics to come.
Keywords: COVID-19; Pandemic; Pathogenesis; Autopsy